Issues of partial credit in mathematical assessment by computer - C. E. Beevers; D. G. Wild; G. R. McGuire; D. J. Fiddes; M. A. Youngson (Association for Learning Technology, 1999)
The CALM Project for Computer Aided Learning in Mathematics started at Heriot-Watt University in 1985. hi the first phase of the project CAL materials were created in calculus with each topic structured around Theory, Worked Examples, Motivating Examples and a Test. Students chose most readily to work through the Test section questions, welcoming the chance to assess their own progress. In addition, the teachers could view class progress. The weekly tests were designed from banks of questions with randomized parameters in each question. These questions prompted students for a mathematical answer and asked them to type in the response on one line using a style similar to computer languages such as Pascal. Students of engineering and science took only a short time to adjust to this approach. The routines developed in those early stages of CALM meant that testing could be more meaningful and did not rely on the more usual multiple-choice format favoured by so many computer projects. Over the years 1989-1992 CALM developed techniques to trap predictable wrong answers and this form of self-testing proved to be a powerful learning aid for students. Nevertheless, some problems which are discussed in greater detail in later sections remained.